A survey of managed care strategies for pregnant smokers. (1st September 2000) - Barker, Dianne C; Robinson, Lucy A; Rosenthal, Abby C
Abstract : OBJECTIVE: The purpose of this study was to measure the content and comprehensiveness of pregnancy specific smoking cessation strategies within managed care organisations (MCOs) responding affirmatively to the national 1997-98 Addressing Tobacco in Managed Care (ATMC) survey. DESIGN: This cross sectional follow up study consisted of a fax survey sent to medical directors and a 37 question telephone survey of program overseers about the smoking cessation strategy. SUBJECTS: 147 MCOs identifying a pregnancy specific smoking cessation strategy on the 1997-98 ATMC survey served as the initial sample; 88 MCOs of 128 eligible plans completed both components, with a response rate of 69%. RESULTS: Pregnancy specific smoking cessation strategies varied. 40% of respondents used the Agency for Health Care Policy and Research guidelines for clinical smoking cessation to design their strategy. Strategies included self help materials, quit classes, telephone support and brief counselling by providers, linkages to quality improvement efforts, and use of patient databases for outreach. Only 42% offered a postpartum relapse prevention element. Lack of patient interest, competing clinic priorities, and the lack of a smoker identification system were the most problematic barriers to implementing strategies, common to at least a quarter of respondents. A majority ranked best practice manuals and web site linkages as the most useful form of technical assistance, followed by peer-to-peer counselling, regional workshops, newsletters, on-site assistance, and national conferences. CONCLUSIONS: The survey provides the first profile of prenatal tobacco treatment strategies in managed care. While design limitations prevent generalisation of these results to all MCOs, such information can help guide technical assistance to plans interested in reducing smoking among pregnant women.